Fiction : - Gordon, Jane Bachman (McGraw - Hill, 1999)
This collection of classic and contemporary short stories is organized around the basic elements of fiction (plot, setting, character, point of view and tone, theme, and style). Biographical author sketches, explanatory footnotes, discussion questions, writing topics, and a glossary of terms guide students' understanding.